Avaliação da toxicidade e do potencial angiogênico do látex de pinhão manso - (:unkn) unknown (Universidade Estadual de Goiás, 2015)
Much of the technological innovations in biomedical areas and biotechnology applied to health related to the use of biomaterials. Although thousands of plants with potential therapeutic value, just over 15% of these species are scientifically proven results. Regarding lactíferas plants, an estimated 12 to 35 thousand species present virtually unknown pharmacological potential. In Brazil the use of Jatropha genus plants in folk medicine, is inserted in different procedures, but in addition to use in folk medicine there are scientific studies that prove the potential anticancer, antibacterial and anti-inflammatory Jatropha curcas of, family kind of Euphorbiaceae. This study aimed to evaluate the toxic capacity, cytotoxic and genotoxic (bioassay with Allium cepa), and the potential angiogenic (test with membranes embryonated chicken egg chorioallantoic) of Jatropha latex in different concentrations. In toxicity tests, concentrations were 0.1%, 0.5% and 1% and compared to negative control (distilled water) and, in the cyto- and genotoxicity tests also compared to the positive control (sodium azide 2g/L). The results show the latex capacity even in small concentrations to alter the normal range in cell function, both the macroscopic level (toxicity) and microscopic (cytotoxicity and genotoxicity). Regarding the potential angiogenic the run test used higher concentrations, 25%, 50% and pure latex, obtaining similar results to inhibitory control both the imaging evaluation, with reduced vasculature, as the histological test, the occurrence of factors such as hyperemia , presence of inflammatory cells and neovascularization, which shows the anti-angiogenic potential of Jatropha latex.
Keywords: Mutagenicidade; biomaterial; potencial farmacológico; bioensaios; mutagenicity; biomaterial; pharmacological potential; bioassays; CIENCIAS AGRARIAS